A young female adult patient with an ischaemic stroke and patent foramen ovale: a case report and literature review - GJorcheva, Irena; Arsovska, Anita (Croatian Academy of Sciences and Arts – Medical Sciences, 2022)
Strokes in young adults are relatively rare. We present a 36-year old female patient, who came to the urgent neurological outpatient office of the Clinic for neurology due to symptoms presented two hours prior to the examination. The symptoms consisted of inability to move the left arm, partial motor weakness of the left leg, slurred speech and difficulty swallowing. The urgent CT scan result was normal. Despite the fulfilled conditions, thrombolysis was not possible. Brain MRI results revealed a small hypersignal lesion in FLAIR with diffusion restriction on the right, cortically to subcortically, in gyrus praecentralis. The genetic testing for cardiovascular diseases showed that the patient is a homozygote for the mutation C677T (OMIM® 607093.0003) in the gene for methylenetetrahydrofolate reductase (MTHFR) and heterozygote for the mutations eNOS G894T and LTA. The following gene polymorphisms were typed: PAI 5G/4G, HPA1 1b/1a, ACE deletion/insertion, EPCR A4600G A/A, EPCR G4678C C/G and APOE E3/E4. Trans-esophageal echocardiography discovered an aneurysm of the interatrial septum, with a present PFO channel, with a diameter of 6.8 mm. The bubble test was positive, and there were no visible thrombi in the left auricle. The cardiologist recommended closing of the PFO with a device and therapy with acetylsalicylic acid. The cause of the stroke was found and measures for secondary prevention were taken. The patient has returned to her work and private obligations. She upholds neurological consultations regularly and her recovery is closely observed.
Keywords: ischaemic stroke; young adult; patent foramen ovale; MTHFR; C677T homozygote